1991
DOI: 10.1007/bf00591380
|View full text |Cite
|
Sign up to set email alerts
|

The use of endoscopic ultrasound in determining the depth of cancer invasion in patients with gastric cancer

Abstract: Endoscopic ultrasonography (EUS) was performed in 110 patients with gastric cancer to examine the depth of cancer invasion. The normal gastric wall has a five-layer structure on EUS. In 19 lesions, changes on EUS were limited to the first and/or second layers, suggesting that invasion was limited within the mucosa. In 91 lesions, changes were evident in the third or deeper layers. Alterations in the EUS appearance could be divided into two types: type A, with destruction of the layered structure and type B wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…The reported accuracy of preoperative depth diagnosis of M-cancer varies from 69.2% to 92.2% [45][46][47][48][49][50][51][52][53], which is consistent with the range in the present results (67%-89.9%). The presence of ulcer fibrosis in the lesion is well known to hamper diagnosis [51][52][53][54], but we did not collect data on ulceration in this study. A discrepancy between macroscopic (intraoperative) and histological (postoperative) diagnosis of node involvement has been reported [55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 90%
“…The reported accuracy of preoperative depth diagnosis of M-cancer varies from 69.2% to 92.2% [45][46][47][48][49][50][51][52][53], which is consistent with the range in the present results (67%-89.9%). The presence of ulcer fibrosis in the lesion is well known to hamper diagnosis [51][52][53][54], but we did not collect data on ulceration in this study. A discrepancy between macroscopic (intraoperative) and histological (postoperative) diagnosis of node involvement has been reported [55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 90%
“…The reported predictive value for EGC with EGD, MDCT, and EUS were 67.3-92.4% [5,15], 76.5-100.0% [12,13,[16][17][18], 57.1-100.0% [13,[19][20][21][22][23], respectively in various studies. The overall accuracy for EGC of EGD, MDCT and EUS were 83.6-96.8% [5,6,15,24], 77.8-94.1% [12,13,[16][17][18]25], 76.2-95.6% [7,13,[19][20][21][22]26,27], respectively. The values in this study were relatively higher than the results from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore high performance of CT for T stage may be caused by high-end CT scanner like MDCT and meticulous method for vigorous gastric distension with gas and water [16,28]. With respect to the N stage, the reported predictive value for N(À) of MDCT and EUS were 66.7-85.7% [11,13,16,18] and 54.8-95.0% [11,13,[19][20][21][22][23]29], respectively, and the overall accuracy for N(À) were 68.9-85.5% [11,13,16,18] and 65.9-98.0% [7,11,13,[20][21][22][23]27], respectively, similar to those observed in this study. The relatively low predictive value of N(À) was due to the lack of reliable CT and EUS criteria for metastatic nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 29 studies, with 2500 patients, that reported on the accuracy of EUS staging for gastric cancer between 1988 and 2009; 37-65 21 [37][38][39][40][41][43][44][45]47,48,[50][51][52][53]56,57,59,[62][63][64][65] used radial ultrasound probes, three 49,58,60 used linear array probes and five 42,46,54,55,61 did not report the type of probe ( Table 1). As the reported accuracy of linear array probes for both T and N stages did not differ from that of the rest, we include them here.…”
Section: Gastric Cancersmentioning
confidence: 99%